Europac Group : an equity valuation - Santos, Miguel Maria Moreira Rato de Andrade (2017)
The following Master Thesis aims to answer the question “What is YE16 Europac Group Fair Value?”, compare it with BPI Equity Research, find a fair price and provide buy or sell recommendations. This Dissertation begins with a research concerning valuable literature and models for Europac’s Group Valuation. After collecting the necessary data and formulating a deep company analysis, supported by the investor relations department, I was able to understand how should I approach this firm. In this context, by using the models I consider more appropriate (FCFF Method and Multiples), and building consistent assumption and forecasts, I was able to find the fair value of the firm. Thus, the FCFF approach resulted in a share price for Europac of 5,64€, compared with a closing market share price of 5,25€ at the 31th December 2016. The Multiples approach did not precisely correspondend to the DCF valuation, arriving at different values (EV/EBITDA 5,42€; PE 6,99€;). In this context, I arrived at a fair value price per share for Europac of 5,64€. It is, therefore, my believe that the share is underpriced and the market is going to adjust in 2017. To conclude, I present a comparasion analysis with BPI Equity Research, highlighting the relevant differences in the assumptions and figures forecasted, in order to justify my conclusions regarding the fair price. Hence, I finish this dissertation providing a buy recommendation so that investors can make a capital gain.